PELATIHAN KEPEMIMPINAN MELALUI PASKIBRA UNTUK MENINGKATKAN DISIPLIN DAN KERJA SAMA TIM UNTUK SISWA MTsN KOTA SERANG - Umayah, Umi Kulsum; Husni, Mohamad; Idayu, Riyanthi; Komarudin, Mochamad Fahru; Afriani, Raden Irna; Lestari, Dini Martinda (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
Leadership training through Paskibra at MTsN Serang City is designed to improve students' leadership skills, discipline and teamwork. This activity aims to build student character through a theoretical and practical approach involving marching training, cooperation simulations, and strengthening leadership values. This training is carried out in the form of community service as a form of higher education's contribution in supporting the formation of a young generation who is superior and has noble morals. The results of the training showed a significant increase in students' understanding of responsibility, decision making, and coordination in teams. Students also experience increased discipline, reflected in their ability to comply with the schedule and rules applied during training. Apart from that, this program is relevant to the vision of Islamic-based character education, instilling the values ??of responsibility, trust and cooperation for the common good. This training is effective in supporting the formation of students' character as future leaders. With continuous development and evaluation, this program can become a model for improving the quality of character education in other schools, especially through Paskibra extracurriculars